2019
DOI: 10.1080/13574809.2019.1686350
|View full text |Cite
|
Sign up to set email alerts
|

Shared mobility and urban form impacts: a case study of peer-to-peer (P2P) carsharing in the US

Abstract: This paper advances the understanding of peer-to-peer (P2P) carsharing within the broader context of shared mobility and its connection to the built environment in the US through a survey conducted in 2014 (n = 1,151). Eleven percent of respondents used carpooling/ridesharing more, and 19% avoided a vehicle purchase due to P2P vehicle access in urban areas. Nevertheless, P2P carsharing has the potential to operate in a range of land-use environments and could be an important strategy to further deemphasize car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Another, more recent carsharing type is (2), the P2P carsharing, where private owners of cars offer the temporary usage of their own private car to others, typically facilitated by an internet platform (cf. Shaheen et al, 2019 ).…”
Section: Introduction Motivationmentioning
confidence: 99%
“…Another, more recent carsharing type is (2), the P2P carsharing, where private owners of cars offer the temporary usage of their own private car to others, typically facilitated by an internet platform (cf. Shaheen et al, 2019 ).…”
Section: Introduction Motivationmentioning
confidence: 99%
“…A simulation model was proposed in [306] to analyze and improve the peer-to-peer service. Shaheen et al [307] studied peer-to-peer dynamics in the USA also considering the usage of automated vehicles. Travel behavior was analyzed in [308], where it resulted that vehicle owners tend to decrease travel distance and to move further using other modes.…”
Section: Peer-to-peer Car-sharingmentioning
confidence: 99%
“…A 2004 survey of carshare members in the United States and Canada found that 87 percent of the members were white (Burkhardt and Millard-Ball 2006), similar to the rate found among early adopters in Philadelphia (Lane 2005). A recent survey of P2P carshare members, a relatively new service in the United States, also found that whites were overrepresented (as well as Asians), while African Americans and Latinos were underrepresented relative to the population (Shaheen, Martin, and Bansal 2018). Studies in Ithaca (New York) and Portland (Oregon) found that the share of white members was comparable to the population, though that was predominantly white (Dotson and Blair 2011; Dill, McNeil, and Howland 2017).…”
Section: Access To and Use Of Vehicle Sharing By Different Populationsmentioning
confidence: 99%